2010
DOI: 10.1111/j.1399-3038.2009.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to main roads during pregnancy and the risk of allergic disorders in Japanese infants: The Osaka Maternal and Child Health Study

Abstract: Miyake Y, Tanaka K, Fujiwara H, Mitani Y, Ikemi H, Sasaki S, Ohya Y, Hirota Y. Residential proximity to main roads during pregnancy and the risk of allergic disorders in Japanese infants: The Osaka Maternal and Child Health Study.
Pediatr Allergy Immunol 2010: 21: 22–28.
© 2009 John Wiley & Sons A/S The role of traffic‐related air pollution in the initiation of allergic disorders in children is still not clearly understood. The present prospective study examined the relation between proximity of the home durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…The outcomes evaluated in these studies varied between heart diseases [5][6][7][8][9] , respiratory diseases 5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] , gestational outcomes [24][25][26][27][28] , allergies and changes in the immunological system [29][30][31] , thrombosis 32 , cancer and leukemia [33][34][35][36][37] , lead contamination 38 and mortality in general 39 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes evaluated in these studies varied between heart diseases [5][6][7][8][9] , respiratory diseases 5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] , gestational outcomes [24][25][26][27][28] , allergies and changes in the immunological system [29][30][31] , thrombosis 32 , cancer and leukemia [33][34][35][36][37] , lead contamination 38 and mortality in general 39 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Miyake et al 28 found a low residential mobility in Neyagawa, Japan. A total of two interviews were conducted with the pregnant women, one in the prenatal period and the other between the 2 nd and 9 th months after birth.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1.74 (95% CI: 1.15-2.62) for 15 μg/m 3 increase in NO 2 exposure in utero (Deng et al, 2015a). A prospective cohort study in Japan found that the distance between the residence and the nearest main road, a surrogate for trafficrelated pollution, during pregnancy was associated with an increased risk of doctor-diagnosed asthma (Miyake et al, 2010).…”
Section: Tablementioning
confidence: 99%